Genetic relationships among temperament, immune function, and carcass merit in beef cattle - Bates, Kerri E.; Weaber, Robert L.; Bormann, Jennifer M.; Moser, Daniel W.; Salak-Johnson, J. L.; Chase, C. C. L.; Peel, R. K.; Van Campen, H.; Loneragan, G. H.; Wagner, J. J.; Bodhireddy, P.; Prayaga, K.; et al. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2014)
Cattle producers historically have selected for docile temperaments simply for management convenience because calmer animals are conducive to safe environments for their peers as well as their handlers. As many producers would acknowledge, there seems to be a relationship between temperament and health, and calmer cattle tend to frequent the working chute for treatment of disease less often. Positive correlations have been found in cattle between temperament traits (chute scores, pen scores, and chute exit velocities) and cortisol concentration in the blood, suggesting that more excitable cattle are easily stressed (Curley et al., 2006; Cooke et al., 2009). In addition, Curley et al. (2007) found that easily excitable animals sustain elevated cortisol concentrations for a longer duration and had greater pituitary and adrenal responses following a stressor than calm cattle. Temperamental cattle have significantly higher mean temperament responses at all points (Oliphint, 2006). Higher basal serum cortisol concentrations may suggest that easily excitable cattle are chronically stressed (Curley et al., 2007), possibly resulting in a compromised immune system, illness, and decreased fat and protein deposition. Common measures of cattle temperament are pen scores, chute scores, and exit velocities. Temperament appears to be moderately heritable, with estimates ranging from 0.15 to 0.44 (Burrow and Corbet, 2000; Kadel et al., 2006; Schrode and Hammack, 1971; Stricklin et al., 1980; Fordyce et al., 1988). If genetic correlations are found between temperament and production traits or immunological factors, they may aid cattle breeders in producing profitable cattle. Such relationships have been found between exit velocity and hot carcass weight (r = -0.54), exit velocity and marbling score (r = 0.10), exit velocity and yield grade (r = -0.22) (Nkrumah et al., 2007), and post-weaning weight gain and exit velocity (Weaber et al., 2006). Bovine respiratory disease (BRD) susceptibility has been estimated to be lowly heritable (Muggli-Cockett et al., 1992; Snowder et al., 2005, 2006, 2007; Schneider et al., 2008). This study was conducted to further investigate the genetic relationships between cattle temperament measured by chute score and exit velocity, immunological factors, and a range of economically relevant performance traits.
Keywords: Beef; Temperment; Carcass traits; Genetics